IMPLEMENTATION OF CLINICAL SUPERVISION WITH A LESSON STUDY APPROACH THROUGH ZOOM MEETING IN IMPROVING TEACHER PROFESSIONALISM - Darwis B (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study aims to improve teacher professionalism through the application of clinical supervision with a lesson study approach conducted via Zoom meetings in Kampar District, Kampar Regency. This research employed an action research design using the lesson study approach. Data were collected through questionnaires and observation sheets, including teaching simulation scores and Learning Implementation Plan design scores. The research subjects consisted of 36 teachers in Kampar District. Data were analyzed using descriptive analysis. The results showed that in the first cycle, the average score was 80.08 (good category), and in the second cycle, it increased to 83.85 (good category). These findings indicate that the continuous and consistent application of clinical supervision with a lesson study approach via Zoom meetings significantly improves learning quality and enhances teacher performance and professionalism.